Comparison of short term outcomes of open and laparoscopic cholecystectomy. Issue 1 (March 1995) - Cleary, R; Venables, C W; Watson, J; Goodfellow, J; Wright, P D
Abstract : OBJECTIVE--To compare the three month outcome of open and laparoscopic cholecystectomy. DESIGN--Prospective assessment of outcome for a series of patients encompassing the introduction of the laparoscopic technique. SETTING--One teaching hospital. PATIENTS--269 patients admitted for open cholecystectomy between January 1989 and March 1992 and 122 admitted for laparoscopic cholecystectomy between January 1991 and March 1992. MAIN MEASURES--Patients' reported symptoms and self assessed scores with the Nottingham health profile before operation and at three month follow up. Incidence of complications and adverse events after discharge. RESULTS--Similar improvements in symptom rates and health scores were seen regardless of surgical technique. A lower rate of postoperative complications was seen in the patients given laparoscopic surgery (6/95(6%) v 45/235(19%)), and their mean length of stay was lower (4.5 v 9.8 days). Similar results were obtained when the analysis was restricted to a subset of fairly uncomplicated cases (patients aged 60 or less without other illnesses on admission who were not undergoing emergency or urgent surgery), which constituted a larger proportion of the group given laparoscopy (35/95(37%) v 40/235(17%)). Between these two groups no significant difference was seen in the frequency of relevant readmissions to hospital or visits to general practitioners or accident and emergency departments. CONCLUSION--Ideally, a new surgical technique would be evaluated in a randomised trial. In the absence of such a trial, this observational study provides some evidence that the switch from open to laparoscopic cholecystectomy has brought benefits, particularly in terms of reduced length of stay in hospital. A range of clinical and patient derived indicators suggests that these gains have not been associated with a reduction in the quality of the outcome at three months.